ANALISA PENANGANAN KOMPLAIN PEREMAJAAN KWH METER 1 PHASA PASCABAYAR DAN PRABAYAR PELANGGAN DI WILAYAH PT. PLN PERSERO UNIT LAYANAN PENGADUAN (ULP) GEDANGAN - Di Ajeng Ayu Shafira Putri; Diah Ayu Sanggarwati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This research explores the role of PT PLN Persero in meeting the electricity needs of the Indonesian people. As a state-owned enterprise in the electricity sector, PT PLN Persero is the largest electricity service provider that has a significant impact in supporting daily life. The research method used is descriptive qualitative, which aims to provide an objective picture of the company's role. The respondents interviewed, including the director and two employees from the Gedangan Complaint Service Unit (ULP), have a high level of responsibility. Their success in handling customer complaints reflects a commitment to quality service. This research details that PT PLN Persero's success in providing electricity lies not only in the technical aspects, but also in the effectiveness of customer complaint management. The findings of this research can serve as a foundation for improvement and enhancement in public services in the electricity sector.